2016
DOI: 10.15835/nsb819752
|View full text |Cite
|
Sign up to set email alerts
|

Weeds Cause Losses in Field Crops through Allelopathy

Abstract: A large number of weeds are known to be associated with crops and causing economic losses. Weeds interfere with crops through competition and allelopathy. They produce secondary metabolites known as allelochemicals, which belong to numerous chemical classes such as phenolics, alkaloids, fatty acids, indoles, terpens etc. However, phenolics are the predominant class of allelochemicals. The allelochemicals release from weed plants takes place through leaf leachates, decomposition of plant residues, volatilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Many invasive species also use allelopathy as an added settlement asset, as already mentioned in the introduction. Allelochemical substances are responsible for modulating the basic and complex physiological mechanisms that occur in plants at various stages of their development [48]. The results of studies on the impact of allelochemical compounds on the increase in the invasiveness of certain plants in ecosystems confirm the important ecological role of this type of interactions [49,50].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Many invasive species also use allelopathy as an added settlement asset, as already mentioned in the introduction. Allelochemical substances are responsible for modulating the basic and complex physiological mechanisms that occur in plants at various stages of their development [48]. The results of studies on the impact of allelochemical compounds on the increase in the invasiveness of certain plants in ecosystems confirm the important ecological role of this type of interactions [49,50].…”
Section: Discussionmentioning
confidence: 82%
“…The extracts had a greater inhibitory effect on cucumber than on sunflower [59]. The reduced germination capacity observed in both cases could be a consequence of a disturbed hormonal balance, especially a change in the activity of gibberellic acid, which regulates the synthesis of de novo amylase during the germination process, as well as disturbances in protein synthesis, activity of enzymes, photosynthesis, and respiration [48]. From an ecological point of view, in highly competitive environments, even slight germination delays can be an advantage for the aggressive neighbor and affect the adaptability of alien taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of germinability and biomass production might be attributed to the water soluble phenolics present in the water extracts of weeds (Zohaib et al, 2014a). Reduced germinability might have occurred as a result of perturbed hormonal balance, protein synthesis, enzyme activity, photosynthesis and respiration (Zohaib et al, 2016). It has been observed that depressed and delayed germination by allelochemicals (phenolics) happens due to the suppression of respiration by hindrance of respiratory enzymes and the enzymes involved in oxidative pentose phosphate pathway (Muscolo et al, 2001) which is necessary for synthesis of RNA and DNA, production of ATP and generation of intermediates for Calvin cycle in early stages of greening of leaves during seedling germination (Taiz and Zeiger, 2002).…”
Section: Allelopathic Effect Of Water Extracts Of Weeds On Germinabilmentioning
confidence: 99%
“…This was further evidenced by the fact that root/shoot ratio and correlation analysis showed a positive relationship between root dry biomass and root shoot ratio (Table 6). This decreased inhibition of root biomass production might be due to reduced respiration losses in roots because of hindrance in activities of respiratory enzymes caused by allelochemicals (Zohaib et al, 2016).…”
Section: Allelopathic Effect Of Weed Residues On Emergence and Biomasmentioning
confidence: 99%
See 1 more Smart Citation